Nursing experiences in specialized services in child and adolescent mental health: a systematic review of qualitative studies - Luz, Priscilla de Oliveira; de Souza, Adriana Almeida; Boska, Gabriella de Andrade; Cardoso, Marilia Mastrocolla de Almeida [UNESP]; Candido, Bruna de Paula; de Oliveira, Márcia Aparecida Ferreira (FapUNIFESP (SciELO), 2023)
Objective: to synthesize evidence from qualitative studies on nursing experiences regarding child and adolescent mental health care in specialized services. Method: a systematic review with meta-synthesis of qualitative studies according to JBI guidelines. CINAHL, EMBASE, MEDLINE, LILACS, PSYCinfo, Scopus and Web of Science databases were used. The findings were classified according to the level of reliability and credibility and categorized by similarity between contents. Results: 229 articles were identified, and five were included in the final sample and organized into the categories: Emotional impact; and Understanding nursing role. The level of evidence found was moderate. Final considerations: nursing experiences are permeated by emotional exhaustion, feelings of frustration and difficulty in understanding their professional role. The need for training spaces that qualify this care is highlighted.
Experiencias de enfermería en servicios especializados en salud mental infantil y adolescente: revisión sistemática de estudios cualitativos
Experiências da enfermagem em serviços especializados em saúde mental infantojuvenil: revisão sistemática de estudos qualitativos
Keywords: Adolescent; Child; Mental Health; Nursing; Systematic Review